2013
DOI: 10.35800/jasm.1.2.2013.7280
|View full text |Cite
|
Sign up to set email alerts
|

The role of Bakasang as immunostimulant on non-specific immune response in Nile Tilapia (Oreochromis niloticus)

Abstract: Bakasang produced from fermented fish’s offals contains some type of Lactic Acid Bacteria (LAB) and have potential as imunostimulant. LAB that can live and grow in the digestive tract of fish serve to suppress the growth of pathogenic bacteria, and produce metabolites that can stimulate the activity of the immune system. The purpose of this study was to examine the effect of bakasang as imunostimulant and to determine the optimal dose of bakasang for increasing non-specific immune response and growth in tilapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…As said Agustina et al 2006that increasing the number of leukocytes is one indicator of the increase in the non-specific immune system of the fish's body. Pangaribuan et al (2013) research results showed the increasing number of fish leukocytes to 77.92 % after the treatment of lactic acid bacteria (bekasang) for 4 weeks compared to fish that were not given the LAB.…”
Section: Total Of Leukocytes After Immersion With Lab Isolates and Thmentioning
confidence: 96%
“…As said Agustina et al 2006that increasing the number of leukocytes is one indicator of the increase in the non-specific immune system of the fish's body. Pangaribuan et al (2013) research results showed the increasing number of fish leukocytes to 77.92 % after the treatment of lactic acid bacteria (bekasang) for 4 weeks compared to fish that were not given the LAB.…”
Section: Total Of Leukocytes After Immersion With Lab Isolates and Thmentioning
confidence: 96%
“…Bakasang adalah produk fermentasi yang dibuat dari jeroan ikan. Bakteri Asam Laktat (BAL) pada bakasang dapat meningkatkan konsentrasi asam-asam amino seperti asam aspartate, asam glutamate, prolin dan valin sebagai pemicu sistem imun ikan dan pertumbuhan ikan (Ijong et al, 1996;Ingratubun et al, 2013;Pangaribuan et al, 2013;Pinoke et al, 2015). Sampai saat ini belum ada POLITEKNIK NEGERI NUSA UTARA…”
unclassified